Selected Socio-Ecological Factors Affecting Entomophagy in Nambale Sub County, Kenya - Omemo, James (JOOUST, 2021)
Entomophagy describes the practice of eating insects by humans. Globally, there are over 3000 ethnic groups that consume insects. The objective of this study was to determine selected socio ecological factors affecting entomophagy in Nambale Sub County. The study assumed cross sectional survey design. The target population was 298 farmers who were trained on Climate variability and weather conditions adaptation and conservation agriculture with a sample size of 171. The data was analyzed using descriptive statistics and chi square tests, with the aid of Statistical Package for the Social Science (SPSS) version 20. Multi-linear regression was used to test the significance of association between the independent variables and the dependent variable while correlation was used to quantify the strength of the relationship between the continuous variables. Results were displayed using Tables, percentages and frequency distribution. Analysis of data was done using entomophagy, the practice of insect consumption, as the dependent variable against socio economic, information availability and Climate variability and weather conditions as independent variables. The findings from124 respondents were that entomophagy was significantly related with socio-economic factors (p<0.05) information availability and Climate variability and weather conditions (p<0.05).The Gender of respondents (OR=2.2;95% C1=1.74-4.3), p=0.008 occupation (OR=2.5;95% CI=(1.5-5.9), p=0.032, education levels (OR=0.9;95% CI=(0.4-0.9),p=0.039, land ownership type (OR=3.46;95% CI=(1.92-7.58), p=0.000), household size (OR=2.46;95% CI=(1.33-5.31), p=0.012, size of land (OR=0.67;95% CI= (0.36-2.28), p=0.721, and the researcher concluded that the above factors positively influenced practice of eating insects. It was also found that socio economic factors had a positive influence on entomophagy (t = 2.260, p=0.026) both information availability, and Climate variability and weather conditions had positive influence on entomophagy (information availability: t = 6.697, p = 0.000; Climate variability and weather conditions: t = 4.047, p=0.000). The study concludes that socio economic factors and information availability have a statistically significant effect on consumption of edible insects. Additionally, Climate variability and weather conditions had a statistical significant influence on entomophagy in Nambale Sub-County. The study recommends that there should be efforts to equip residents of Nambale subcounty with knowledge regarding the benefits of entomophagy both on nutrition and ecological aspects for socio economic wellbeing. There is need to put a regulatory framework in place to facilitate the monitoring of edible insects’ value chain to enhance the confidence and trust of the consumers as well as to enable interested corporates to join edible insects’ value chain. Specifically, the study recommends understanding the interrelationship between the flying termites’ ecology and entomophagy as key in enhancing socio and economic wellbeing of the people in this region. This will help in understanding and managing the climate variability effects on the flying termites in order to adopt appropriate utilization measures.
Keywords: Entomophagy